2016
DOI: 10.1130/g38327.1
|View full text |Cite
|
Sign up to set email alerts
|

Shock-metamorphosed rutile grains containing the high-pressure polymorph TiO2-II in four Neoarchean spherule layers

Abstract: At least 17 spherule layers are presently known within stratigraphic units deposited between ca. 3.47 and 2.49 Ga. The spherule layers contain varying amounts of formerly molten, millimeter-sized and smaller spherules. The aggregate thickness of spherules in these layers commonly ranges from ∼1 cm to as much as a few decimeters. Several lines of evidence support the interpretation that the spherule layers represent distal impact ejecta layers. Previously, only one shock-metamorphosed grain (quartz) had been do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 27 publications
3
32
0
Order By: Relevance
“…Recently, shock-metamorphosed grains containing rutile and TiO 2 -II have been documented from four Neoarchean spherule layers-Carawine spherule layer (CSL), Jeerinah spherule layer (JSL), Monteville spherule layer (MSL), and Bee Gorge spherule layer (BGSL)-deposited between ~2.65 and ~2.54 billion years ago. [16] These grains, which provide unambiguous physical evidence to further support an impact origin for these layers [16], comprise the samples for this study.…”
mentioning
confidence: 77%
“…Recently, shock-metamorphosed grains containing rutile and TiO 2 -II have been documented from four Neoarchean spherule layers-Carawine spherule layer (CSL), Jeerinah spherule layer (JSL), Monteville spherule layer (MSL), and Bee Gorge spherule layer (BGSL)-deposited between ~2.65 and ~2.54 billion years ago. [16] These grains, which provide unambiguous physical evidence to further support an impact origin for these layers [16], comprise the samples for this study.…”
mentioning
confidence: 77%
“…All of these sedimentological features observed in the Graensesø spherule layer have been observed in debris-flow deposits (see Nardin et al [1979] and references therein). It is now clear that the Graensesø spherule layer has several sedimentological characteristics in common with several other Precambrian spherule layers (see, e.g., Simonson 1992;Simonson et al 1999;Hassler and Simonson 2001;Hassler et al 2005) that have a confirmed impact origin (Rasmussen and Koeberl 2004;Simonson et al 2009;Smith et al 2016). Rudnick and Gao (2003).…”
Section: Physical Evidence Of Impact Eventmentioning
confidence: 95%
“…In fact, only one quartz grain with planar deformation features has been reported from any APB or Early Archean spherule layer and it is from the Jeerinah layer in the Hamersley Basin (Rasmussen and Koeberl 2004). However, the heavy mineral fraction of the Monteville layer has yielded multiple grains of an a-PbO 2 -structured TiO 2 phase (TiO 2 II); this is a highpressure polymorph produced by shock metamorphism during large impacts (Smith et al 2016). Grains of this high-pressure TiO 2 polymorph also occur in three Hamersley spherule layers including the two correlated with the Monteville layer (Smith et al 2016).…”
Section: Stratigraphic Context and Sedimentary Characteristicsmentioning
confidence: 99%
“…However, the heavy mineral fraction of the Monteville layer has yielded multiple grains of an a-PbO 2 -structured TiO 2 phase (TiO 2 II); this is a highpressure polymorph produced by shock metamorphism during large impacts (Smith et al 2016). Grains of this high-pressure TiO 2 polymorph also occur in three Hamersley spherule layers including the two correlated with the Monteville layer (Smith et al 2016). attributed the formation of the Monteville layer to a succession of related events triggered by a large (roughly Chixculub-scale) marine impact.…”
Section: Stratigraphic Context and Sedimentary Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation